Opportunities and Obstacles Faced During Work From Home in Teaching Faculties - Poonam Yadav1 , Sharadha Ramesh, Merlin Suji1 , Leeja Bonny Thomas1 , Stephina Fernandis1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction- The lockdown period amid Covid -19 has given the opportunity to the teaching faculties towork from home and to practise teaching learning activities using various online pedagogies (Zoom, WebEx,Google classroom, Google meet etc) to fill the knowledge gap which may transpire if the teaching learningactivities are ignored and not taken earnestly. Hence taking this in consideration and prioritizing the need oflearning activities to be carried in the virtual methods mostly all teaching faculties in various institutes haveplanned itinerary with the online teaching learning session hour by hour and day by day and also assignedassignments to the students to evaluate the effectiveness of their teaching. Methodology:A Non-ExperimentalDescriptive Research Approach “. The study was conducted among various teaching institutes of PuneCity. The selection of sample was based on easy geographical accessibility, cooperation, and availabilityof samples.The sample size for study was 100,selected by using Non Probability Convenience SamplingTechnique from various teaching institutes of Pune City who met the inclusion criteria.. Objective:1.Toassess the opportunities with work from home in teaching faculties from selected institutes of Pune City 2.Toassess the obstacles faced with work from home in teaching faculties from selected institutes of Pune City3.To associate the demographic variables with the opportunities and obstacles of work from home in teachingfaculties from selected institutes of Pune City.Result :The analysis asserts that the opportunities relatedto personal growth were sometimes applicable for 83% and was often applicable for 17 % of the teachingfaculties, work opportunities for majority of the teaching faculty’s i.e. 82 % were often applicable and foronly 18% of them these opportunities were applicable some times. Work obstacles were often applicable for53 % of teaching faculties and sometimes applicable for 47 % of teaching faculties. Technological obstacleswere often applicable to 88% of teaching faculties and for 12 % it was applicable sometimes. Conclusion:Work from home related to teaching faculties is associated with various opportunities and obstacles howeverit proposes that work from home can be given to teaching faculties also as it is more opportunistic to theteachers as well to the institutes.